Os processos de avaliação do ensino superior nos cursos de Serviço Social: limites, possibilidades e resistências - Martine, Sandra Augusta (2019)
The aim of this thesis is to discuss the Higher Education evaluation processes in the Social Services course regarding its limitations, possibilities and resistance. This study has the following goals: to discuss the evaluation processes present in Brazilian Higher Education and its corresponding impacts on Social Services courses; to analyze the manner in which these processes are stablished, related to one another and used for the commodification of Education; to understand what is the stand of (interviewed) Social Services courses coordinators regarding the National Higher Education Evaluation System (SINAES); to identify motions that seek to change and offer resistance to the commodification of Education and its consequential debilitation. In order to do so, the study recaptures the historical course of Brazilian Education as well as the evaluation system since the Law of Directives and Basis for National Education (LDB) in 1996 and the creation of the SINAES (2004) until present day as to clarify the evaluation processes - including its internal and external aspects, its apparatus and strategies – while discussing its impact on the Social Services courses. A research of qualitative nature has been conducted for the gathering of empirical data through semi-structured interviews at Academic Training Units (UFAs). The scope of the research consists in three (03) Higher Education Institutions – two (02) private institutions located in the city of São Paulo (SP) and one (01) public institution located in the city of Santos (SP). The subjects who have been interviewed are three (03) Social Services course coordinators and one (01) social worker who is an examiner for the Anísio Teixeira National Educational Research and Studies Institute (INEP/MEC). Through the analysis of the empirical research data results, the study could reveal the limitations and possibilities in Higher Education evaluation processes and identify the possible resistance